PERENCANAAN JADWAL INDUK PRODUKSI DENGAN MENGGUNAKAN LINIER PROGRAMING PADA PERUSAHAAN PUPUK ORGANIK âXYZâ - ., Marcahyono (DINAMIKA DOTCOM, 2013)
Consumer demand for an fluctuations tastes of the market is following the constraints in planning and scheduling because the effect on production costs and inventory costs incurred. Organic Fertilizer company "XYZ" is an organic fertilizer manufacturer producing a wide range of organic fertilizers. The amount of manure produced by the company often does not match the amount of consumer demand, so often there is excess and shortage of production. Master production schedule (MPS) is an overview of the planning period, including forecasts of a request, the plan offers, ending inventory, and the promised quantity available or a statement of what the product will be made, how much and when it will be made. Conclusions obtained Master Production Schedule of organic fertilizer products for the next 6 pencanaan period in January, February, March, April, May and June.Â keywords: planning, organic fertilizer, forecasting and MPS